Mesostigmata as biological control agents, with emphasis on rhodacaroidea and parasitoidea - Castilho, Raphael C. [UNESP]; Venancio, Renan; Narita, João Paulo Z. (Springer Nature, 2015)
The Mesostigmata is a large mite order corresponding to about 20 % of all known mite species. These are found in different habitats, but are most abundant and diverse in the soil. Several mesostigmatid groups have been little studied, especially for not being abundant or for being difficult to handle, especially those living in the soil. Knowledge about the diversity of soil mites is still very small in most of the world. Considering just the number of described mesostigmatid species (let aside the number of undescribed species), the number of biological and ecological studies is very limited. Available studies most often are restricted to the evaluation of the ability of particular species to feed on pre-determined food sources. A few have received some attention, among which two superfamilies of the infraorder Gamasina, Rhodacaroidea (in the hyporder Dermanyssiae) and Parasitoidea (in the hyporder Parasitiae). This chapter comprises the biological and ecological information regarding the Mesostigmata.